CHARACTERISTICS OF EDUCATION OF THE YOUNG GENERATION IN AN INFORMED SOCIETY - D. M. Mamatkulov (Journal Park Publishing, 2022)
The article discusses the specifics of our time, the rapid pace of information exchange and the need to approach the education of young people in this process, taking into account the specifics of the time. It is scientifically based on the fact that the education of young people requires such competencies as media literacy, independent thinking (critical analysis), leadership, eco-culture, adaptability to social change.It is known that until our recent history, certain types of information were transmitted from one address to another by means of couriers, birds, caravans. These carriers spent hours, days, or even months delivering the information to their destination.
Keywords: information; media literacy; independent thinking